Recent updates on perturbation analysis of the KALIMER-600 TRU burner - Pham , Nhu Viet Ha; Yoo, Jaewoon; Lim, Jae Yong; Kim, Sang Ji (Nuclear Science and Technology, 2013)
Sodium void worth and the Doppler coefficient, which are very important safety parameters in safety analysis of the KALIMER-600 TRU burner, should be carefully evaluated. A perturbation analysis for the TRU burner has thus been performed using the perturbation method, not only to make sure the reactivity feedbacks meet the predetermined design targets but also to obtain insight into the actual physical processes in response to severe coolant voiding accidents. The more detailed information on the actual physical phenomena that can be achieved, the more helpful it can be to the safety design and analysis of the TRU burner. Hence, a perturbation code, PERT-K, has been developed by the Korea Atomic Energy Research Institute based on the diffusion code, DIF3D,to allow reactivity effect breakdown calculations for fast reactor analysis. This paper presents recent updates on a perturbation analysis of the KALIMER-600 TRU burner using DIF3D and PERT-K. The currently developed isotope-wise reactivity module of PERT-K is described along with an analysis of the scenarios of whole core voiding and fuel temperature change in the TRU burner. The perturbation results are believed to be useful for further optimization of the passive safety characteristics of the TRU burner.